KNOWING INDONESIAN LANGUAGE FOR NON-NATIVE SPEAKERS: FOUNDATIONS FOR BEGINNERS - Khairunissa; Jamaluddin Nasution; Pivi Turbana Br Ginting; Setiyo Wibowo; Selviani Barus (Rahis Cendekia Indonesia, 2025)
Indonesian as a Foreign Language (it is usually called as BIPA – Bahasa Indonesia bagi Penutur Asing) plays an essential role in introducing the Indonesian language and culture to the international community. This article discusses the basics of BIPA learning, from introducing vocabulary and common expressions used in daily communication to understanding the cultural contexts associated with the Indonesian language. With an interactive and easy-to-understand approach, this material aims to help foreign speakers communicate effectively in various social situations, such as in the workplace, education, and everyday life. It is expected that BIPA learning will accelerate the adaptation process for foreign speakers and enhance their understanding of Indonesian cultural values